2020
DOI: 10.46624/ajptr.2020.v10.i6.008
|View full text |Cite
|
Sign up to set email alerts
|

Design of Experiments (DoE) - Based Enhanced Quality by Design Approach to Hydrolytic Degradation Kinetic Study of Capecitabine by Eco-friendly Stability Indicating UV-Visible Spectrophotometry

Abstract: Capecitabine is an anti-metabolite class of anti-neoplastic drug that is converted to fluorouracil in body tissue. Numbers of stability indicating chromatography method such as HPLC, HPTLC etc.have been reported for stability study of capecitabine. But the chromatography methods are tedious, time and solvent consuming methods. Hence, stability-indicating UV-visible spectroscopy method has been developed for hydrolytic degradation kinetic study of capecitabine using design of experiments (DoE)-based enhanced qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Analytical Eco-Scale and GAPI approaches were used to estimate an analytical method's greenness [ 33 35 ]. The proposed approach is a great green method of analysis with few laboratory’s needs, according to the two methods (Table 10 ; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Analytical Eco-Scale and GAPI approaches were used to estimate an analytical method's greenness [ 33 35 ]. The proposed approach is a great green method of analysis with few laboratory’s needs, according to the two methods (Table 10 ; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The data were also subjected to response surface methodology to determine the influence of mobile phase composition, flow rate, and column oven temperature on dependent variables. The probable trial runs using 3 3 Box Behnken designs are shown in Table 2.…”
Section: Optimization Of Developed Rp-hplc Methods With Design Space ...mentioning
confidence: 99%
“…Literature survey reveals that various methods have been reported for capecitabine individually or in combination with other drugs those are UV 3,6,12,15 HPLC 8,14 , stability indicating 2,4,15 , stability by LC-MS 16 , Stability UV by QbD 17,18 , but no one has developed RP-HPLC by Quality by Design method of these drug, which is fast, simple, and sensitive with less run time and good peak symmetry. Finally, the established method was validated with respect to specificity, linearity, precision, accuracy, robustness, LOD and LOQ according to ICH guidelines.…”
Section: Figmentioning
confidence: 99%